How colonial animals evolve - Simpson, Carl (Sci Adv, 2020)
The evolution of modular colonial animals such as reef corals and bryozoans is enigmatic because of the ability for modules to proliferate asexually as whole colonies reproduce sexually. This reproductive duality creates an evolutionary tension between modules and colonies because selection operates at both levels. To understand how this evolutionary conflict is resolved, we compared the evolutionary potential of module- and colony-level traits in two species of the bryozoan Stylopoma, grown and bred in a common garden experiment. We find quantitatively distinct differences in the evolutionary potential of modular and colony traits. Contrary to solitary organisms, individual traits are not heritable from mother to daughter modules, but colony traits are strongly heritable from parent to offspring colonies. Colony-level evolution therefore dominates because no evolutionary change can accumulate among its modules.